In-vitro study on the competitive binding of diflunisal and uraemic toxins to serum albumin and human plasma using a potentiometric ion-probe technique - Davilas, A.; Koupparis, M.; Macheras, P.; Valsami, G. (JOURNAL OF PHARMACY AND PHARMACOLOGY, 2006)
The competitive binding of diflunisal and three well-known uraemic toxins (3-indoxyl sulfate, indole-3-acetic acid and hippuric acid) to bovine serum albumin (BSA), human serum albumin (HSA) and human plasma was studied by direct potentiometry. The method used the potentiometric drug ion-probe technique with a home-made ion sensor (electrode) selective to the drug anion. The site-oriented Scatchard model was used to describe the binding of diflunisal to BSA, HSA and human plasma, while the general competitive binding model was used to calculate the binding parameters of the three uraemic toxins to BSA. Diflunisal binding parameters, number of binding sites, n(i) and association constants for each class of binding site, K-i, were calculated in the absence and presence of uraemic toxins. Although diflunisal exhibits high binding affinity for site I of HSA and the three uraemic toxins bind primarily to site II, strong interaction was observed between the drug and the three toxins, which were found to affect the binding of diflunisal on its primary class of binding sites on both BSA and HSA molecules and on human plasma. These results are strong evidence that the decreased binding of diflunisal that occurs in uraemic plasma may not be solely attributed to the lower albumin concentration observed in many patients with renal failure. The uraemic toxins that accumulate in uraemic plasma may displace the drug from its specific binding sites on plasma proteins, resulting in increased free drug plasma concentration in uraemic patients.